Antiplasmodial Activity, Cytotoxicity, and Active Compounds Analysis of Active Fraction of Harmsiopanax aculeatus Leaves from Maluku, Indonesia - Turalely, Rachel; Mustofa; Hertiani, Triana; Wijayanti, Mahardika Agus (HAYATI Journal of Biosciences, 2025)
The leaves of the H. aculeatus plant are known as a traditional antimalarial medicinal plant in Maluku. Several studies have reported on the leaf activity of this plant, but studies on in vitro and in vivo antiplasmodial activity and the compounds in the active fraction (F7) of H.aculeatus leaf have not been reported. This study aims to determine the antiplasmodial activity of the F7 of H. aculeatus leaves and to analyze the compounds contained therein. In vitro, antiplasmodial activity was tested on Plasmodium falciparum strain FCR3 using a microscopic method. A cytotoxicity test was performed on Vero cells using an MTT assay. In vivo, the antiplasmodial activity of F7 was carried out using the 4-day suppressive test method by treating Swiss mice infected with P. berghei. Analysis of the compounds in an F7 was done using spray reagent and UV Vis DAD and HPLC DAD-MS with a UV detector. The results showed that the F7 was very active in vitro (IC50 of 0.7 µg.ml-1) and in vivo (ED50 of 2.49 mg.kg BW-1.d-1) also selectively (SI of 8159.94) inhibited the growth of Plasmodium. The F7 contains a group of essential oils, triterpenoids, phenolic compounds, and flavonoids after being analyzed using spray reagents. Based on the analysis results, five compounds were identified: fomoxanthone, cyclopentene, microspherone, indole 3-carbaldehyde, and naamine. In addition, seven compounds were not identified.